Social institutional dynamics of seed system reliability: the case of oil palm in Benin. - AKPO, Essegbemon; CRANE, TODD; STOMPH, Tjeerd-Jan; TOSSOU, COCOU RIGOBERT; KOSSOU, KODJO DANSOU; VISSOH, VINASSÉHO PIERRE (My University, 2014)
Seed system reliability is of major importance in farming. Whereas earlier studies analysed mainly annuals, this study focuses on a perennial. Oil palm in Benin was chosen as a case study because farmers complained about non-hybrids (dura and pisifera) in plots allegedly planted with 100% hybrid (tenera). This study assessed the reliability of the oil palm seedling supply system over past decades and its main drivers. An event ecology approach was used to identify causal mechanisms accounting for the observed variation in oil palm types on smallholder plots. A total of 378 plots belonging to 248 farmers that were allegedly planted with tenera between 1969 and 2009 were sampled, and shell thickness of fruits was assessed to determine whether palms were tenera, pisifera, or dura. The proportion of tenera varied with seedling supply source, farmers’ geographic position, seedling purchase price, and year of planting. The proportion of tenera decreased with year of planting. Socio-institutional mechanisms associated with the observed variation in smallholder plots were national policy change, local arrangements for seedling supply to smallholder farmers, and farmers’ personal characteristics. The implications of the observed decrease in the reliability of the seedling supply system are discussed.
Keywords: event ecology; institutions; seedling quality; smallholders; oil palm; policy change; West Africa